Capturing commemoration: the 1916 Easter Rising web archive project. Issue 1 (3rd April 2018) - Kunze, Svenja; Power, Brendan
ABSTRACT: This paper outlines a collaborative project between three UK Legal Deposit Libraries, the Library of Trinity College Dublin, University of Dublin, the Bodleian Libraries, University of Oxford, and the British Library, to create a web archive collection of material relating to the one hundredth anniversary of the 1916 Easter Rising. From a curatorial perspective, it discusses the potential of themed web archive collections for researching commemorative events, outlines the evolving understanding of archival material, reviews the project, and explores the technical, legal, and methodological problems and opportunities that emerged as the project progressed. It highlights the challenges that arose from collaborating across multiple jurisdictions with differing arrangements surrounding non-print legal deposit, and the impact of institutional and legislative frameworks on collection building.